2019
DOI: 10.26418/jhl.v7i4.37836
|View full text |Cite
|
Sign up to set email alerts
|

KEDALAMAN LUBANG INOKULASI DAN UKURAN DIAMETER POHON UNTUK PEMBENTUKAN GUBAL GAHARU PADA TANAMAN Aquilaria malaccensis Lamk.

Abstract: Research on the induction of the sapwood of agarwood has been extensively studied, but this has not yet resulted in the dept standard of hole of inoculation and the diameter of trees in order to produce the best sapwood. Therefore, this study aimed to study the depth of the effective inoculation hole to accelerate the formation of agarwood cambium or sapwood in various tree diameters, and to know the interaction of agarwood induction. This research was conducted in Sekadau Hilir district. The design of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…That is, the improvement of one character will improve another. The same study's results were shown in Aquilaria malaccensis aged 4 years [33].…”
Section: Genetic Correlationsupporting
confidence: 76%
“…That is, the improvement of one character will improve another. The same study's results were shown in Aquilaria malaccensis aged 4 years [33].…”
Section: Genetic Correlationsupporting
confidence: 76%
“…According to the analysis result that the concentrations of IAA and yeast extracts were not significantly affected the shoot's number of agarwood. Wardatutthoyyibah et al (2015) declared that the treatment without auxins can increase the number of shoots that it was not significantly different from the treatment using auxins. Figure 4 shows that the combination of IAA 1 mgL -1 and yeast extract 200 mgL -1 (A2R1) have the highest average number of shoots among other treatments by 2.33.…”
Section: Number Of Shootsmentioning
confidence: 99%
“…Gaharu adalah komoditas produksi hutan non-kayu dalam bentuk damar wangi (aromatic resin) yang terkandung dalam sel kayu, karena adanya infeksi jamur dari suku Ascomycetes dan Deuteromycetes (Azren et al, 2018;Chong et al, 2015;Faisal et al, 2020;Mohamed et al, 2014;Nagajothi et al, 2016;Tabata et al, 2003;Triadiati et al, 2016;Try et al, 2017) atau infeksi bakteri (Chipa & Kaushik, 2017; Nguyen & Nguyen, 2014) atau senyawa kimia (Yan et al, 2019, paten CN1330230C).…”
Section: Pendahuluanunclassified